Genotype identity has a more important influence than genotype diversity on shoot biomass productivity in willow short‐rotation coppices. Issue 8 (11th May 2018) - Hoeber, Stefanie; Arranz, Clara; Nordh, Nils‐Erik; Baum, Christel; Low, Matthew; Nock, Charles; Scherer‐Lorenzen, Michael; Weih, Martin
Abstract: Willow ( Salix spp.) short‐rotation coppice is commercially grown to produce lignocellulosic biomass to meet renewable bioenergy demands. Most commercial willow coppices are grown in stands of a single genotype, but biomass productivity may be greater in mixed communities, and the productivity in mixed communities may depend on the specific genotypes involved. We assessed the biomass production of four different Salix genotypes ("Björn, " "Jorr, " "Loden, " "Tora") grown without additional nutrient fertilization during one cutting cycle at three locations in Europe (Uppsala in Sweden, Rostock and Freiburg in Germany) in plots of pure and mixed communities. We evaluated (i) the effect of genotype diversity on shoot biomass productivity, including the evidence for complementarity and selection effects; (ii) the influence of individual genotypes on mixed community productivity; and (iii) the productivity of individual genotypes in response to pure vs. mixed culture. Mean shoot biomass production after the first cutting cycle decreased in the order Rostock (8.7 Mg ha −1 ) > Freiburg (6.9 Mg ha −1 ) > Uppsala (5.7 Mg ha −1 ), with values similar to those for other nonfertilized willow stands after the first growth cycle. Consistently across all three locations, increasing genotype diversity did not significantly affect shoot biomass production. Using Bayesian statistics, the addition of the genotypes "Jorr" and "Loden" was predicted to enhance shoot biomass production, while "Tora" and "Björn" are more likely to reduce shoot biomass production in mixed communities. In addition, we found evidence for a negative selection effect due to the genotype "Tora" performing better in mixed than in pure communities in two of the sites (Freiburg, Uppsala). In conclusion, our results imply that increasing genetic richness has no negative effect on productivity and that there is a potential to design site‐specific genotype mixtures of short‐rotation coppice promoting both high genetic diversity and high biomass production. Abstract : The shoot biomass production of Salix genotypes ('Loden' and 'Tora') either increased or decreased in mixed compared to pure communities, and the pattern varied between trial locations (Freiburg and Rostock in Germany, Uppsala in Sweden).